Estudos in silico dos modos de ligação dos hormônios tireoidianos T3 e T4 com a Proteína Transportadora Albumina Sérica Humana HSA - Barbosa, Elisa Guimarães (2024)
In the present work, the binding mode and molecular interactions between thyroid hormones (T4, T3 and the positional isomers of T3 – T3IP) and the transporter protein (HSA) were investigated. T4 has 4 iodine atoms and T3 has 3. Analysis of the crystallographic structures of the T4-HSA complexes (1HK1,1HK2-R218H, 1HK3-R218P - with fatty acids and 1HK4, 1HK5-R218H- without fatty acids) was carried out. The knowledge acquired was used in the study of molecular docking to understand T3 since there is no crystallographic structure of HSA with T3, with T3 being the active form of thyroid hormone in target cells. It was observed that HSA is capable of differentiating T4 from T3. Another important point was to study 3 cases of HSA-T4 and HSA-T3 complexes, R128, R218H, R218P and explain the difference in HSA-hormonal ligand affinity. In the case of the T3 ligand, which has 3 iodine atoms, with a specific position, 4 positional isomers, T3IP, were evaluated. Docking studies showed that these compounds are different compared to HSA. The presence of fatty acids in the crystallographic complexes of the native protein and R218H mutant protein affected the availability of binding sites, limiting the interaction with T4 to a single site (Cleft). The analysis of T3 positional isomers (T3IP) showed that the structural flexibility of the ligands is an important factor in determining interactions with HSA. The findings of this study can be applied in the development of therapeutic strategies aimed at transporting thyroid hormones in conditions of genetic mutations or metabolic disorders. Detailed understanding of the differences in affinity between T3 and T4 and the influence of mutations in HSA provides a solid basis for future research focused on modulating the bioavailability of these hormones. The results presented here serve as a starting point for experimental investigations that can validate the trends observed in silico studies and explore new applications in the field of endocrinology and biotechnology.